Towards an Infrastructure Description Language for Modeling Computing Infrastructures - Ghijsen, M.; van der Ham, J.; Grosso, P.; de Laat, C. (2012 IEEE 10th International Symposium on Parallel and Distributed Processing with Applications, 2012)
This paper describes the Infrastructure and Network Description Language (INDL). The aim of INDL is to provide technology independent descriptions of computing infrastructures. These descriptions include the physical resources and the network infrastructure that connects these resources. The description language also provides the necessary vocabulary to describe virtualization of resources and the services offered by these resources. Furthermore, the language can be easily extended to describe federation of different existing computing infrastructures, specific types of (optical) equipment and also behavioral aspects of resources, for example, their energy consumption. Before we introduce INDL we first discuss a number of modeling efforts that have lead to the development of INDL, namely the Network Description Language, the Network Markup Language and the CineGrid Description Language. We also show current applications of INDL in two EU-FP7 projects: NOVI and GEYSERS. We demonstrate the flexibility and extensibility of INDL to cater the specific needs of these two projects.